Target-triggered catalytic hairpin assembly-induced core−satellite nanostructures for high-sensitive “off-to-on” SERS detection of intracellular microRNA - Liu, Conghui (2020)
Surface-enhanced Raman scattering (SERS) technology is emerging as a powerful molecules detection method with distinct advantages of high stability, good specificity, and low background signal compared with current prevailing fluorescence technique. However, the relative low sensitivity of SERS limits its wide applications. Engineered metallic nanoparticle aggregates with strong electromagnetic hot spots are urgently needed for low abundant molecules SERS detection. Herein, a microRNA (miRNA)-triggered catalytic hairpin assembly (CHA)-induced core–satellite (CS) nanostructure with multiple hot spots and strong electromagnetic field in nanogaps is designed. The unique plasmonic CS nanostructure is constructed by plasmonic Au nanodumbbells (Au NDs) as core and Au nanoparticles (Au NPs) as satellites, and it possesses enhanced electromagnetic field compared to that of Au NPs-Au nanorods (Au NRs) CS and Au NPs only. The “off-to-on” SERS strategy leads to a wide linear miRNA detection range from 10–19 to 10–9 M with a limit of detection (LOD) down to 0.85 aM in vitro. Intracellular accurate and sensitive miRNAs SERS imaging detection in different cell lines with distinct different miRNA expression levels are also achieved. The proposed SERS platform contributes to engineering metallic nanoparticle aggregates with strong electromagnetic intensity and has potential application in quantitative and precise detection significant intracellular molecules.